Trapped magnetic flux in superconducting niobium samples - S. Aull; O. Kugeler; J. Knobloch (Physical Review Special Topics. Accelerators and Beams, 2012)
Trapped magnetic flux is known to be one cause of residual losses in bulk niobium superconducting radio frequency cavities. In the Meissner state an ambient magnetic field should be expelled from the material. Disturbances such as lattice defects or impurities have the ability to inhibit the expulsion of an external field during the superconducting transition so that the field is trapped. We have investigated the effect the treatment history of bulk niobium has on the trapped flux and which treatment leads to minimal flux trapping. For that purpose, we measured the fraction of trapped magnetic flux in niobium samples representing cavities with different typical treatment histories. The differences between single crystal and polycrystalline material as well as the influence of spatial temperature gradients and different cooling rates were investigated. In addition, the progression of the release of a trapped field during warm-up was studied. We found that heat treatment reduces trapped flux considerably and that single crystal samples trap less flux than polycrystalline niobium. As a consequence, the single crystal sample with 1200°C baking trapped the smallest amount of field which is about 42%. Moreover, the release of the trapped field during warm-up was observed to progress over a broad temperature range for the baked single crystal samples.